Enhanced thermostability of nattokinase by rational design of disulfide bond - Kongfang Yu; Liangqi Chen; Yaolei Tang; Aixia Ma; Wenhui Zhu; Hong Wang; Xiyu Tang; Yuan Li; Jinyao Li (Microbial Cell Factories)
Abstract Nattokinase, the thrombolytically active substance in the health food natto, nevertheless, its lower thermostability restricts its use in food and pharmaceutical applications. In this study, two heat-resistant variants of nattokinase, designated 50–109 (M1) and 15–271 (M2), were successfully obtained by introducing a disulfide bonding strategy. Their half-lives at 55℃ were found to be 2.50-fold and 5.17-fold higher, respectively, than that of the wild type. Furthermore, the specific enzyme activities of the variants, M1 and M2, were also increased by 2.37 and 1.66-fold, respectively. Meanwhile, the combination of two mutants increased the thermostability of nattokinase by 8.0-fold. Bioinformatics analyses indicated that the enhanced thermostability of the M1 and M2 variants was due to the increased rigidity and structural contraction of the overall structure. Finally, the fermentation process of mutant M1 was optimized to increase the expression of nattokinase. Study provides substantial molecular and theoretical support for the industrial production and application of nattokinase.